Blurring the Boundaries or Muddying the Waters? - Aston, Sally; Jackson, Dot (Design and Technology Education: An International Journal, 2009)
This paper outlines reflections by two tutors in Initial Teacher Education on ways design and technology (D&T) has been included in cross-curricular modules at our institution. These modules were a new addition to our courses in response to a conviction by tutors that crosscurricular teaching and learning in primary schools is important for children’s education and well being. We felt that this approach would support a move towards a more creative curriculum. Often we found that students were unfamiliar with cross-curricular teaching and learning and we discuss how we have been developing strategies and pedagogies to support their understanding of this approach. We are convinced that, in order to raise the status of D&T there is a need to provide exciting and relevant contexts for learning subject specific knowledge and skills, as well as those which cross curricular boundaries.